Volatile sulphur compounds composition of monovarietal white wines - Moreira, Nathalie (2010)
The sulphur compounds composition of wines produced experimentally from six white cultivars (Alvarinho, Loureiro, Trajadura, Pedernã, Azal Branco and Avesso) was evaluated during two consecutive vintages. Results show that wines could be differentiated according to their sulphur compounds content. In general, Loureiro, Trajadura and Pedernã cultivars led to wines with low concentrations of sulphur compounds; however, Loureiro wines were characterised by significant amounts of dimethyl sulphone, whereas Trajadura wines possessed a high content of 3-(methylthio)propyl acetate and 4-(methylthio)-1-butanol. Alvarinho and Avesso wines showed high levels of S-methyl thioacetate, 3-mercapto-1-propanol, 3-(ethylthio)-1-propanol and 3-methylthiopropionic acid. Significant amounts of 2-methyltetrahydrothiophen-3-one, cis- and trans-2-methyltetrahydrothiophen-3-ol were also found in Avesso wines. Azal Branco wines were low in 3-(methylthio)propyl acetate and 2-(methylthio)ethanol, and high contents in S-methyl thioacetate, 3-mercapto-1-propanol and 2-mercaptoethanol. A linear discriminant analysis of sulphur compounds levels showed a differentiation of wines according to their varietal origin.